(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The environmental cost management focus on continuous improvement of processes and the various activities of the organization in order to improve the environmental performance by producing an environmentally friendly products lead to a competitive advantage for the organization and supports the activities of their sustainability. The study was carried out in Bagel cement factory, one of the pioneer projects in Yemen in manufacturing field, The study found the need to develop a separate section for environmental management in order to put plans and environmental policies and the introduction of a special division in the Department of costs cares about Management practices cost and measure environmental costs, also give solutions to environmental problems and diagnosis of opportunities to achieve cost savings and improve the environmental performance to actively contribute in sustainable environmental development.